Plasmodium falciparum with pfhrp2 and pfhrp3 gene deletions in asymptomatic malaria infections in the Lake Victoria region, Kenya - Takatsugu Okai; Chim W. Chan; Achyut KC; Protus Omondi; Kelvin Musyoka; James Kongere; Wataru Kagaya; Gordon Okomo; Bernard N. Kanoi; Yasutoshi Kido; Jesse Gitaka; Akira Kaneko (Tropical Medicine and Health)
Abstract Malaria rapid diagnostic tests (RDTs) targeting the Plasmodium falciparum histidine-rich protein 2 (PfHRP2) are widely used to diagnose P. falciparum infection. However, reports of P. falciparum strains lacking PfHRP2 and the structurally similar PfHRP3 have raised concerns about the utility and reliability of PfHRP2-based RDTs. This study investigated the presence of P. falciparum with pfhrp2 and/or pfhrp3 gene deletions among infected residents in the Lake Victoria region, Kenya. Four cross-sectional malaria, surveys were conducted in four sites (Suba South, Mfangano, Kibuogi, and Ngodhe) from September 2018 to January 2020. P. falciparum infections were detected using a PfHRP2-based RDT, microscopy, and PCR on 9120 finger-prick blood samples. Samples negative by RDT but positive by PCR were selected for PCR amplification of pfmsp1 and pfmsp2 to confirm the quality and quantity of P. falciparum DNA. Samples positive for both pfmsp1 and pfmsp2 were included for detection of deletions of exons 1 and 2 in pfhrp2 and pfhrp3 PCR. The multiplicity of infection (MOI) was determined as the higher allele count between pfmsp1 and pfmsp2. Logistic regression analysis was performed to analyze the association between pfhrp2 and/or pfhrp3 deletions and demographic and infection variables. Of the 445 RDT-negative and PCR-positive samples, 125 (28.1%) were analyzed for pfhrp2 and pfhrp3 deletions. Single pfhrp2 deletion, single pfhrp3 deletion, and pfhrp2/3 double deletions were detected in 13 (10.4%), 19 (15.2%), and 36 (28.8%) samples, respectively. Single pfhrp2 deletion was found in all sites while single pfhrp3 deletion was found in all sites except Kibuogi. The majority of samples with pfhrp2 and/or pfhrp3 deletions were submicroscopic (73.5%), asymptomatic (80.9%), and monoclonal (80.9%). Polyclonal infection was significantly (p = 0.022) associated with a lower odds of pfhrp2/3 double deletion, suggesting detection of intact pfhrp2/3 in mixed infections. We report the presence of P. falciparum with pfhrp2/pfhrp3 double deletions among asymptomatic and submicroscopic infections in Kenya. Our findings highlight the need for active monitoring of pfhrp2 and pfhrp3 deletions at the community level to improve malaria detection and control in the region.